Chapter 1 Digital technologies and women's empowerment casting the bridges - Lechman, Ewa (Taylor & Francis, 2021)
"The near-ubiquitous spread of ICT offers unprecedented opportunities for social and economic agents, reshapes social and economic structures and drives the emergence of socio-economic networks. This book contributes to the growing body of literature and present state of knowledge, offering the reader broad evidence on how new information and communication technologies impact women's economic and social empowerment and hence have an impact on overall welfare creation. More specifically, it concentrates on demonstrating how ICT may become 'empowering technologies' through their implementation. The book is designed to provide deep insight into the theoretical and empirical evidence on ICT as a significant driver of women`s social and economic development. Special focus is given to examining the following broad topics: channels of ICT impact on women`s development; the role of ICT in enhancing women`s active participation in formal labor markets; examples of how ICT encourages education, skills development, institutions development et alia, and thus contributes to women's social and economic empowerment, as well as case-based evidence on ICT`s role in fostering women's equality. The primary audience for the book will be scholars and academic professionals from a wide variety of disciplines but mainly those who are concerned with addressing the issues of economic development and growth, social development, the role of technology progress in the context of broadly defined socio-economic progress."